Ethical Issues and Indigenous Knowledge Production and Use in Sub-Saharan Africa in the 21st Century - Ondari, Ezra Okemwa (My University, 2014)
This paper addresses the ethical issues which relate to the sharing, use, access, research and personal as well as social benefit of indigenous knowledge produced in sub-Saharan Africa. Close to two decades into the 21st century, which supposedly ushered in the “knowledge/information society,” communities in sub-Saharan Africa still depend on indigenous knowledge to have access to information which they use for making crucial decisions and solve day-to-day critical problems. In the information age, indigenous knowledge may be the only source of information that communities and individuals in subSaharan Africa have control over and are comfortably familiar with. Indigenous knowledge is recognized as having relevance to sub-Saharan Africa’s people’s daily life, economic development, cultural preservation and political transformation which may lead to poverty reduction in the region that is categorized as one of the least developed, if not the least developed in the world. Important as indigenous knowledge is to communities in sub-Saharan Africa, the issues of ethics relating to access and use of the knowledge do not feature prominently. The broad objectives of this paper include examining the ethics that should be observed when producing indigenous knowledge in sub-Saharan Africa; how the knowledge is shared ethically; who should have access to the knowledge; find out the extent to which research findings in indigenous knowledge may be used to address local concerns such as projects in health, agriculture and education in sub-Saharan Africa; establish how ethical use of the knowledge may lead to sustainable social, economic, technical, cultural and political development in sub-Saharan Africa; and suggest ways of formulating policies which may promote and encourage ethical exploitation and use of indigenous knowledge in sub-Saharan Africa. Methods for collecting data for the paper will include a review of available relevant literature review, seeking views of a few indigenous knowledge practitioners, which will be supplemented by the author’s knowledge of indigenous knowledge systems in sub-Saharan Africa. Findings of the study would add value to the existing body knowledge on the ethical issues relating to the management of indigenous knowledge produced in the sub-Saharan Africa region.
Keywords: Ethics; Indigenous knowledge; Sub-Saharan Africa; Access; Intellectual property; Higher education